Evaluation of Long Term Intake of Citrus aurantifolia Juice on Fertility Indices in Male Wistar Rats - Ahmad, Zainab; Abdullahi, Hauwa; Adamou, Natasha; Umar, Hauwa; Alhassan , Sharif (AlQalam Journal of Medical and Applied Sciences, 2023)
Background and aims. Infertility is one of the most common presentations in gynecological clinics. Male-related factors account for over 30% of all cases. Several factors are known to interfere with fertility promoters and indices, such as drug treatment, environmental toxins, air pollution and stress. Citrus aurantifolia was shown to affect the number of shed ova and sperm cells. This study aimed to determine the effects of long-term intake of Citrus aurantifolia juice (CAJ) on sperm parameters and sex hormones in male Wistar rats. Methods. A total of twenty-four (24) rats were used in the study and were randomly subdivided into 4 groups (n=6). Group I (normal control) received 1 ml/kg distilled water. Group II received 1 ml/kg concentrated CAJ (cCAJ), Group III received 1 ml/kg diluted CAJ (dCAJ) at a 1:1 ratio, and Group IV received 1 ml/kg dCAJ at a 1:2 ratio. The preparations were given daily by gavage for a period of 42 days. Blood and semen samples collected from each rat were subjected to hormonal and seminal fluid analysis. Results. The hormonal assay revealed a significant decrease in prolactin (p=0.0014) and LH (p=0.0124) levels with a significant increase in FSH (p=0.0021) and testosterone (p=0.001) levels in Group II that received cCAJ compared with Group I. The seminal fluid analysis revealed that the mean values of active cells, viable cells, total counts and normal cells in Group II were significantly lower (p value=0.0001) than those in the normal group. However, the mean values significantly increased (p value=0.001) in Groups III and IV but were still lower than those in Group I. Conclusion. The findings of this study indicate a negative effect of the CAJ on male fertility indices with a possible effect on spermatogenesis that may lead to infertility in male adult Wistar rats.